They do it with mirrors [large type] - Christie, Agatha, 1890-1976 (Center Point Pub., 2011)
Miss Jane Marple finds herself investigating murder when, at the urging of Ruth Van Rydock who has premonitions of foul play, she visits Stonygates, home of her friend Carrie Louise Serrocold and a treatment center for juvenile delinquents--Novelist.